Right ventricular function among South East Nigeria children with sickle cell anaemia - Josephat M. Chinawa; Bartholomew F. Chukwu; Awoere T. Chinawa; Edmund N. Ossai; Anthony N. Ikefuna; Ann E. Aronu; Egbuna O. Obidike (BMC, 2020)
Abstract Background Sickle cell anaemia (SCA) is characterized by attendant ischemia-reperfusion injury especially to the heart. Methods The aim of this work is to compare the right ventricular function of children with SCA in steady state (subjects) with those with haemoglobin AA genotype (controls), using echocardiography. It is a cross-sectional study, which echocardiographic measurements to assess right ventricular function among children with SCA and their controls. Results The mean trans annular plane systolic excursion (TAPSE) in subjects, 28.24 ± 5.23 (Z score: 0.258 ± 1.10) was higher than that in control, 25.82 ± 3.59 (Z score: - 0.263 ± 0.80), and the difference in mean was statistically significant, (t = 2.703, p = 0.008). Significantly higher proportion of subjects with sickle cell anaemia had right ventricular dysfunction (Abnormal TAPSE), 25 (50.0%) when compared with those in control, 11 (22.0%), {χ2 = 8.5, p = 0.0035}. A higher proportion of subjects with sickle cell anaemia (25.5%) had Pulmonary hypertension (RVP) when compared with control (2.0%) and the difference in proportions was found to be statistically significant, (χ2 = 11.668, p = 0.001). The prevalence of right ventricular diastolic dysfunction in subjects was 9.8% while control was 0%. Conclusion Children with sickle cell anaemia present with right ventricular dysfunction. Prevalence of right ventricular systolic and diastolic dysfunction were higher in subjects. More of the subjects in this study (25.5%) had pulmonary hypertension.